Formulation and evaluation of mucoadhesive buccal patch of acyclovir utilizing inclusion phenomenon - Ankita Saxena; Gulab Tewari; Shubhini Awasthi Saraf (Brazilian Journal of Pharmaceutical Sciences, 2011)
Mucoadhesive buccal patch releasing drug in the oral cavity at a predetermined rate may present distinct advantages over traditional dosage forms, such as tablets, gels and solutions. A buccal patch for systemic administration of acyclovir in the oral cavity was developed using polymers hydroxy propyl methyl cellulose (K4M), hydroxy propyl methyl cellulose (K15M), sodium carboxy methyl cellulose and poly vinyl pyrolidone (K30), plasticizer poly ethylene glycol (400) and a backing membrane of Eudragit (RL100). The films were evaluated in terms of swelling, residence time, mucoadhesion, release, and organoleptic properties. The optimized films showed lower release as compared to controlled drug delivery systems. Hence, an inclusion complex of acyclovir was prepared with hydrophilic polymer hydroxylpropyl beta-cyclodextrin in the molar ratio of 1:1. The inclusion complex was characterized by optical microscopy, FAB mass spectroscopy, and FTIR spectroscopy. Patches formulated with the acyclovir inclusion complex were evaluated along the same lines as those containing acyclovir alone. The in vitro release data revealed a substantial increase from 64.35% to 88.15% in the case of PS I and PS II batches, respectively, confirming the successful use of inclusion complexes for the formulation of buccal patch of acyclovir. Mucoadesivos bucais liberadores de fármacos para a cavidade oral com taxa de liberação pré-determinada podem apresentar distintas vantagens em relação às formas farmacêuticas convencionais como comprimidos, géis e soluções. Neste trabalho, um adesivo bucal para administração sistêmica de aciclovir através da cavidade oral foi desenvolvido empregando-se os polímeros hidroxipropilmetil celulose (K4M), hidroxipropilmetil celulose (K15M), carboximetil celulose sódica e polivinil pirrolidona (K30), polietilenoglicol plastificado (400) e uma membrana suporte de Eudragit (RL100). Os filmes obtidos foram avaliados em termos de intumescimento, tempo de residência, mucoadesão, liberação e propriedades organolépticas. Os filmes otimizados apresentaram liberação mais lenta em comparação a outros sistemas de liberação controlada. Desta maneira, um complexo de inclusão de aciclovir foi preparado com o polímero hidrofílico hidroxipropil beta-ciclodextrina em proporções molares 1:1. O complexo de inclusão foi caracterizado por microscopia ótica, espectrometria de massas FAB e espectroscopia FTIR. Os adesivos formulados com o complexo de inclusão de aciclovir foram avaliados em paralelo com adesivos contendo aciclovir isolado. Os dados de liberação in vitro revelaram um aumento substancial, de 64,34% para 88,15%, nos lotes PS I e PS II, respectivamente, confirmando o sucesso do uso de complexos de inclusão para a formulação de adesivos bucais de aciclovir.